Quasi-static and dynamic Brazilian testing and failure analysis of a deer antler in the transverse to the osteon growth direction. (February 2023) - Tuncer, Can; Güden, Mustafa; Orhan, Mehmet; Sarıkaya, Mustafa Kemal; Taşdemirci, Alper
Abstract: The transverse tensile strength of a naturally fallen red deer antler (Cervus Elaphus) was determined through indirect Brazilian tests using dry disc-shape specimens at quasi-static and high strain rates. Dynamic Brazilian tests were performed in a compression Split-Hopkinson Pressure Bar. Quasi-static tensile and indirect Brazilian tests were also performed along the osteon growth direction for comparison. The quasi-static transverse tensile strength ranged 31.5–44.5 MPa. The strength increased to 83 MPa on the average in the dynamic Brazilian tests, proving a rate sensitive transverse strength. The quasi-static tensile strength in the osteon growth direction was however found comparably higher, 192 MPa. A Weibull analysis indicated a higher tensile ductility in the osteon growth direction than in the transverse to the osteon growth direction. The microscopic analysis of the quasi-static Brazilian test specimens (tensile strain along the osteon growth direction) revealed a micro-cracking mechanism operating by the crack deflection/twisting at the lacunae in the concentric lamellae region and at the interface between concentric lamellae and interstitial lamellae. On the other side, the specimens in the transverse direction fractured in a more brittle manner by the separation/delamination of the concentric lamellae and pulling of the interstitial lamellae. The detected increase in the transverse strength in the high strain rate tests was further ascribed to the pull and fracture of the visco-plastic collagen fibers in the interstitial lamellae. This was also confirmed microscopically; the dynamically tested specimens exhibited flatter fracture surfaces. Graphical abstract: Image 1 Highlights: Strength of antlers are strain rate sensitive. A higher tensile ductility in the osteon growth axis is observed. Micro-cracking mechanisms operating around the lacunae in the concentric lamellae region enhances toughness of cortical bone. Increased transverse strength at high strain rates due to pull and fracture of the visco-plastic collagen fibers.